Analisis SWOT Pengembangan Wakaf untuk Pasar Tradisional di Yayasan Tanah Wakaf Pasar Paing Surabaya - Yusril Hakiki; Lilik Rahmawati (STAI Terpadu Yogyakarta, 2022)
Research with the aim of explaining the development of productive waqf at the Tanah Waqf Market Paing Foundation Surabaya. The research method in this thesis uses descriptive qualitative methods. The data collection techniques carried out are observation, interview, and documentation techniques. The results showed that the SWOT analysis on the development of productive waqf at the Tanah Waqf Market Paing Foundation Surabaya is the need to increase assets in the form of facilities and equipment needed by traders, forming a beautiful self-managed park to attract people to visit the market, mouth promotion and social media to traders that are intense for the development of their business, traders are not charged parking fees, Because they have paid the rent of the kiosk per month and the officer revoked the right to manage the individual. Analysis of productive waqf development at Yayasan Tanah Wakaf Pasar Paing Surabaya is that the external environment has legal and technological strength factors. Strong law has the power to defend waqf land rights in the improvement of assets or facilities. Meanwhile, technological factors need to be used by existing social media. The internal environment is the establishment of a right-of-use book applied at the Paing Market Waqf Land Foundation.